Pantograph Catenary Contact Force Regulation Based on Modified Takagi-Sugeno Fuzzy Models - Hai, Nguyen Van; Tiem, Nguyen Van; Lan, Le Hung; Vo, Thanh Ha (Engineering, Technology & Applied Science Research, 2023)
In this paper, a new contact force control technique, based on the modified Takagi-Sugeno model and the parallel distributed compensation concept is developed to suppress vibrations between the pantograph and the catenary by regulating the contact force to a reference value, thereby achieving stable current collection. The proposed method uses simple and standard PID and modified Takagi-Sugeno fuzzy controllers. The two controllers guarantee the designed system’s robust stability. Furthermore, based on a simplified pantograph–catenary system model, the comparative simulation results show that variations of the contact force can be almost attenuated. As a result, the system stability is guaranteed, and the performance robustness is verified.